Finite Element Modeling and Performance Evaluation of Bamboo Reinforced Concrete Beams and Columns - Muhammad, B. B.; Mohammed, K.; Muazu, N.; Mohammed, S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
The rising cost and environmental impact of steel reinforcement pose significant challenges to the construction industry. Bamboo, with its favourable mechanical properties and sustainability benefits, offers a promising alternative for reinforced concrete structures. However, accurately predicting its behaviour within concrete requires advanced modelling techniques. This study evaluates the structural performance of bamboo-reinforced concrete (BRC) beams and columns using Finite Element Analysis (FEA) in ABAQUS, validated against experimental data. Three beam configurations and five column configurations, featuring varying bamboo diameters and strip arrangements, were analysed using concrete grades M20 and M25. The results revealed a strong correlation between numerical and experimental outcomes, with correlation coefficients (R²) ranging from 0.985 to 0.999. Experimentally, ultimate failure loads for beams ranged from 2.3 kN to 19.06 kN, while numerical predictions ranged from 2.89 kN to 18.0 kN. For columns, experimental failure loads varied between 127 kN and 357 kN, with numerical estimates deviating by less than 12%. A notable discrepancy of 26% was observed for Beam 3, primarily due to the weak bond between bamboo and concrete; a key limitation highlighted in this study. Overall, the findings demonstrate that finite element modelling can reliably predict the structural behaviour of BRC elements, particularly in lightly loaded applications. The study underscores the critical influence of reinforcement type and arrangement on failure loads and deflections.